2017
DOI: 10.1186/s40795-017-0185-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and E supplementation does not affect heat shock proteins or endogenous antioxidants in trained skeletal muscles during 12 weeks of strength training

Abstract: Background: Supplementation with large doses of antioxidants, such as vitamin C and E, has been shown to blunt some adaptations to endurance training. The effects of antioxidant supplementation on adaptations to strength training is sparsely studied. Herein we investigated the effects of vitamin C and E supplementation on acute stress responses to exercise and adaptation to traditional heavy load strength training. Methods: In a double blind placebo-controlled design, twenty-eight, young, trained males and fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Supplementation with 500 mg vitamin C and 1000 mg vitamin E in elderly women produced no effect on oxidative stress and HSP72 expression, as shown by Simar et al [ 41 ]. Similar data were reported by Cumming et al [ 42 ], after 1000 mg vitamin C and 235 mg vitamin E supplementation in muscle cells. In a previous study on 24 elderly women (12 in the CON group and 12 in the 1000 mg vitamin C SUPP group), who were subjected to the same training regime and for the same period (6 weeks), we observed no changes in the pro/antioxidative balance; however, supplementation increased TAS/TAC accompanied by increased TOS/TOC.…”
Section: Discussionsupporting
confidence: 90%
“…Supplementation with 500 mg vitamin C and 1000 mg vitamin E in elderly women produced no effect on oxidative stress and HSP72 expression, as shown by Simar et al [ 41 ]. Similar data were reported by Cumming et al [ 42 ], after 1000 mg vitamin C and 235 mg vitamin E supplementation in muscle cells. In a previous study on 24 elderly women (12 in the CON group and 12 in the 1000 mg vitamin C SUPP group), who were subjected to the same training regime and for the same period (6 weeks), we observed no changes in the pro/antioxidative balance; however, supplementation increased TAS/TAC accompanied by increased TOS/TOC.…”
Section: Discussionsupporting
confidence: 90%
“…In this sense, a short-term high-dose vitamin C and E supplementation (vitamin C: 2000 mg/day, vitamin E: 1400 IU/day; 4 days) has been effective to attenuate exercise-induced muscle damage and inflammatory response during and after competitive Olympic Taekwondo (TKD) matches in elite athletes [ 53 ]. However, Cumming et al [ 54 ] reported that vitamin C and E supplementation did not affect acute stress responses or long-term training adaptations in the heat shock proteins or endogenous antioxidants among trained adults.…”
Section: Vitamin E As An Antioxidant Supplementmentioning
confidence: 99%
“…Some research has suggested that these substances might help with post-exercise recovery. However, some research suggests that these supplements may not only enhance post-workout adaptations but may slow them down [51]. Moreover, both experienced and untrained athletes' redox homeostasis frequently changes due to anaerobic and aerobic activities.…”
Section: In Terms Of Adaptations To Trainingmentioning
confidence: 99%
“…Biochemical and structural adaptations to ST can help improve health and physical function by increasing SM mass and strength. Biochemical adaptations are more closely linked to effective post-exercise stress management systems such as endogenous antioxidants and heat shock proteins (HSPs) [51,59]. In stressful circumstances like inflammation, OS, ischemia, hypoxia, physical exercise, and fever, HSPs can protect the body's cells by possibly degrading damaged proteins, initiating protein folding, repairing, and refolding misfolded peptides.…”
Section: In Terms Of Adaptations To Trainingmentioning
confidence: 99%
See 1 more Smart Citation